2012
DOI: 10.1155/2012/313120
|View full text |Cite
|
Sign up to set email alerts
|

Application of Anterior Segment Optical Coherence Tomography in Pediatric Ophthalmology

Abstract: Purpose. Application of anterior segment optical coherence (AS-OCT) in pediatric ophthalmology. Methods. Retrospective clinical study case series of 26 eyes of 19 pediatric patients throughout a 21-month period, presenting anterior segment pathologies, were submitted to AS-OCT examination (OCT Visante, 1310 nm, Zeiss), noncontact technique, no sedation requirement. Results. AS-OCT images were obtained from 19 patients (range: 2 months to 12 years). Clinical diagnosis of anterior segment abnormalities included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…In their study, mesodermal dysgenesis (Peters’ anomaly in two eyes) was demonstrated as increased reflectivity of the central cornea (leukoma) associated with local indentation (malformation) of the posterior surface (Descemet's membrane defect), with overall increased stromal reflectivity and thickness. [5] We confirmed the diagnosis of our case based on similar findings in OCT.…”
supporting
confidence: 86%
“…In their study, mesodermal dysgenesis (Peters’ anomaly in two eyes) was demonstrated as increased reflectivity of the central cornea (leukoma) associated with local indentation (malformation) of the posterior surface (Descemet's membrane defect), with overall increased stromal reflectivity and thickness. [5] We confirmed the diagnosis of our case based on similar findings in OCT.…”
supporting
confidence: 86%
“…Cauduro et al 9 have beautifully described the usage of AS-OCT in pediatric ophthalmology in 26 eyes of 19 children with various anterior segment diseases in their article, and have labelled it feasible in clarifying diagnosis, and surgical planning and follow up. Majander 10 et al have utilized this technique with extensive benefit in pediatric eyes of 7 patients with varying causes of congenital corneal opacities.…”
Section: Discussionmentioning
confidence: 99%
“…Cauduro et al point out that in the case of paediatric diagnostics of acquired and congenital defects in the anterior segment, OCT provides invaluable services [ 6 ]. Optical tomography supports a topographic diagnosis of the anatomy of the anterior chamber that accounts for the position of the iris-lens diaphragm.…”
Section: Discussionmentioning
confidence: 99%